Women in the Arab Spring. (c2015) - Kabbout, Lara Said (2015)
What are the root causes of gender inequality in the Arab region? Are corrupt and incompetent regimes responsible for the historic subjugation of Arab women? The Arab Spring appears to have presented an opportunity to end corrupt regimes and pave the way for an era of freedom and equality, which women’s rights advocates have long pursued. This thesis examines the question of whether the Arab Spring, in which Islamists in many countries rose to power, has positively impacted the status of women in the region. A comparative pre-post research study is conducted in order to reveal the impact of Arab Spring on the status of women in Egypt and Syria. Various gender status indicators are utilized to measure the impact. Findings are triangulated by relying on surveys and personal interviews with women leaders in both countries. The results indicate significant deterioration in the status of women since 2011. Moreover, possibilities and political alternatives concerned with the future of Arab women are briefly discussed.